Science societies resources for life in a technoscientific world - Davies, Sarah R. (Bristol University Press, 2025)
Scientific and technical expertise, now largely understood as the ultimate source of authoritative knowledge, are vital to how our societies operate. This punchy introduction to thinking about science-society relations draws on research and concepts to argue for the importance of knowing.